Circumbinary Habitable Zones in the Presence of a Giant Planet - Georgakarakos, Nikolaos; Eggl, Siegfried; Dobbs-Dixon, Ian (Frontiers in Astronomy and Space Sciences, 2021)
Determining habitable zones in binary star systems can be a challenging task due to the combination of perturbed planetary orbits and varying stellar irradiation conditions. The concept of ``dynamically informed habitable zones" allows us, nevertheless, to make predictions on where to look for habitable worlds in such complex environments. Dynamically informed habitable zones have been used in the past to investigate the habitability of circumstellar planets in binary systems and Earth-like analogs in systems with giant planets. Here, we extend the concept to potentially habitable worlds on circumbinary orbits. We show that habitable zone borders can be found analytically even when another giant planet is present in the system. By applying this methodology to {\bf Kepler-16, Kepler-34, Kepler-35, Kepler-38, Kepler-64, Kepler-413, Kepler-453, Kepler-1647 and Kepler-1661} we demonstrate that the presence of the known giant planets in the majority of those systems does not preclude the existence of potentially habitable worlds. Among the investigated systems {\bf Kepler-35, Kepler-38 and Kepler-64} currently seem to offer the most benign environment. {\bf In contrast, Kepler-16 and Kepler-1647 are unlikely to host habitable worlds